Leadership mindset in mental health. (February 2018) - Ng, Lillian; Steane, Richard; Scollay, Natalie
Objectives: The objective of this study was to explore the concept of mindset for psychiatrists who are considering stepping into the leadership arena. Methods: Qualitative themes were extracted from dialogue on leadership development at a Royal Australian and New Zealand College of Psychiatrists forum for early career psychiatrists. Results: Three key themes were identified: adapting to a professional identity as psychiatrists; developing a mindset for leadership; and acting intentionally to seek opportunities for leadership. Conclusions: Shifts in professional identity occur in the transition from trainee to specialist as early career psychiatrists become increasingly aware of broad systemic factors in clinical care. The concept of a mindset, distinct from a skillset of knowledge and expertise, may be an emergent quality for psychiatrists who are seeking to develop their leadership potential.